Feeding strategy shapes gut metagenomic enrichment and functional specialization in captive lemurs. (4th May 2018) - McKenney, E. A.; O'Connell, Thomas M.; Rodrigo, Allen; Yoder, Anne D.
ABSTRACT: Many studies have demonstrated the effects of host diet on gut microbial membership, metagenomics, and fermentation individually; but few have attempted to interpret the relationship among these biological phenomena with respect to host features (e.g. gut morphology). We quantitatively compare the fecal microbial communities, metabolic pathways, and fermentation products associated with the nutritional intake of frugivorous (fruit-eating) and folivorous (leaf-eating) lemurs. Our results provide a uniquely multidimensional and comparative perspective on the adaptive dynamics between host and microbiome. Shotgun metagenomic sequencing revealed significant differential taxonomic and metabolic pathway enrichment, tailored to digest and detoxify different diets. Frugivorous metagenomes feature pathways to degrade simple carbohydrates and host-derived glycosaminoglycans, while folivorous metagenomes are equipped to break down phytic acid and other phytochemical compounds in an anaerobic environment. We used nuclear magnetic resonance based metabolic profiling of fecal samples to link metabolic pathways to fermentation products, confirming that the dissimilar substrates provided in each diet select for specific microbial functions. Fecal samples from frugivorous lemurs contained significantly different profiles of short chain fatty acids, alcohol fermentation products, amino acids, glucose, and glycerol compared to folivorous lemurs. We present the relationships between these datasets as an integrated visual framework, which we refer to as microbial geometry. We use microbial geometry to compare empirical gut microbial profiles across different feeding strategies, and suggest additional utility as a tool for hypothesis-generation.